Morphological and physiological aspects of Hobsonia mirabilis (Peck) Linder, helicosporic hyphomycete reported for the first time from Mexico - Heredia Abarca, Gabriela; Arias Mota, Rosa María; Reyes Estebanez, Manuela (Instituto de Ecología, A.C., 2002)
Hobsonia mirabilis (Peck) Linder, a helicosporous fungus, is recorded for the first time from Mexico. This saprobic, leaf litter species forms white, gelatinous sporodochia on decaying vegetation. The fungus is described and illustrated in situ, and additional information on its morphology in culture is presented. Results of tests of its ability to grow on several carbon sources are also presented.